The Human-Associated Archaeon Methanosphaera stadtmanae Is Recognized through Its RNA and Induces TLR8-Dependent NLRP3 Inflammasome Activation - Vierbuchen, Tim; Bang, Corinna; Rosigkeit, Hanna; Schmitz, Ruth A.; Heine, Holger (Frontiers in Immunology, 2017)
The archaeon Methanosphaera stadtmanae is a member of the gut microbiota; yet, the molecular cross-talk between archaea and the human immune system and its potential contribution to inflammatory diseases has not been evaluated. Although archaea are as bacteria prokaryotes, they form a distinct domain having unique features such as different cell wall structures and membrane lipids. So far, no microbe-associated molecular patterns of archaea which activate innate immune receptors have been identified. By stimulating human myeloid cells with M. stadtmanae and purified archaeal nucleic acids, we identified both the microorganism and its RNA as potent stimuli for the innate immune system. To dissect the recognition and activation pathways induced by M. stadtmanae, human monocytic BLaER1 knockout cells were generated using the CRISPR/Cas9 system targeting components of TLR and inflammasome signaling. Whereas the recognition of M. stadtmanae is mediated by TLR7 and TLR8, activation of the NLRP3 inflammasome depends solely on TLR8 engagement. Notably, this process resembles hallmarks of both the canonical and the recently described alternative inflammasome activation. Thus, we have demonstrated for the first time the specific recognition of and response to an archaeon by human cells at the molecular level.